On the Fundamental Theorems of General Equilibrium. - Maskin, E; Roberts, K (Springer, 2008)
We provide simple generalizations of the three principal theorems of general equilibrium (existence of equilibrium and the two welfare theorems). These enable us to (1) establish equilibrium existence in economies where Walras' Law does not always hold and (2) show that the second welfare theorem follows from a revealed preference argument as simple as that normally used to prove the first welfare theorem.